Implementasi Kebijakan Pengamanan Aset dan Keamanan Lingkungan pada Pusat Pemerintahan Daerah oleh SATPOL PP dan Penanggulangan Kebakaran Provinsi Kepulauan Riau - Doso Saputro, Sugiarto; Akhyary , Edy; Okparizan (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2024)
SATPOL PP plays a role in monitoring and supervising assets at regional government centers, ensuring protection from physical and digital threats, and responding to crises quickly and effectively. In the Riau Islands Province, the government center is consolidated on Dompak Island, which is a strategic location with many administrative activities and public services. This research aims to determine the implementation of the Asset Security and Environmental Security Policy at the Regional Government Center by SATPOL PP and Fire Management in the Riau Islands Province. This research uses a qualitative approach with data collection techniques through observation, interviews and documentation studies. The research results show that SATPOL PP and Fire Management have an important role in monitoring, supervising and protecting assets in regional government centers, especially on Dompak Island, Riau Islands Province. Conclusion, the implementation of asset security and environmental security policies has been carried out in accordance with existing regulations, indicating that there are sufficient efforts to maintain security and order in the area.